2017
DOI: 10.1177/2165143417705353
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Postsecondary Education and Employment Outcomes Using Results From the Transition Assessment and Goal Generator

Abstract: We conducted an exploratory study to investigate the relation between nonacademic behavior constructs measured by the Transition Assessment and Goal Generator (TAGG) and postsecondary education and employment outcomes for 297 high school leavers who completed the TAGG during their high school years. Four of eight TAGG constructs predicted postsecondary educational outcomes: (a) Interacting With Others, (b) Student Involvement in the Individualized Education Program (IEP), (c) Support Community, and (d) Goal Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…IEP meeting participation is an established evidence-based practice with positive impacts on postschool outcomes for youth with disabilities (e.g., Burnes et al, 2018;Martin et al, 2006;Newman, 2004;Wagner et al, 2012;Wehmeyer & Palmer, 2003;Wehmeyer & Schwartz, 1997). In this study, we used selected youth-and parent-reported items from the NLTS2012 that measure IEP meeting participation to conduct an in-depth examination and to better understand differences according to student characteristics based on not only disability but also race, ethnicity, and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IEP meeting participation is an established evidence-based practice with positive impacts on postschool outcomes for youth with disabilities (e.g., Burnes et al, 2018;Martin et al, 2006;Newman, 2004;Wagner et al, 2012;Wehmeyer & Palmer, 2003;Wehmeyer & Schwartz, 1997). In this study, we used selected youth-and parent-reported items from the NLTS2012 that measure IEP meeting participation to conduct an in-depth examination and to better understand differences according to student characteristics based on not only disability but also race, ethnicity, and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in the field of secondary transition have identified evidence-based practices designed to teach academic and transition skills to support posschool attainment as well as identified predictors of postschool success (e.g., Haber et al, 2016;Mazzotti et al, 2021;Test et al, 2009). Active participation of youth in their individualized education program (IEP) meetings is one such evidence-based practice with positive impacts on postschool outcomes (e.g., Burnes et al, 2018;Martin et al, 2006;Newman, 2004;Wagner et al, 2012;Wehmeyer & Palmer, 2003;Wehmeyer & Schwartz, 1997). These and other studies have identified a range of predictors, including those at the student level (e.g., level of school engagement, self-determination skills, selfdirected IEP meetings, functional skills), parent or family (e.g., parent expectations for the child's future, parent involvement in IEP transition meetings), and school-related factors (e.g., access to college-and careerreadiness courses, vocational experiences) that can potentially be addressed by the educational system.…”
mentioning
confidence: 99%
“…Whether SD is defined more behaviorally (Carter et al, 2011;self-management, self-regulation) or from a psychological empowerment perspective (Shogren et al, 2017; primary causal agent in one's life) could affect how SD is measured and taught. In-depth SD transition assessments (Burnes et al, 2018) that take into consideration the unique characteristics of incarcerated youth, particularly those with EBD, could be used to better understand predictive factors related to future employment and postsecondary education. Regardless of how SD is defined, because SD has been shown to contribute to better life outcomes for youth with disabilities (e.g., Halpern et al, 1995), future researchers should examine how SD strategies and curricula can be customized to meet the unique transition needs of incarcerated youth (Houchins, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Haber et al (2016) advanced that work, conducting a meta-analysis on these predictors, and found some difference in employment, education, and independent living outcomes based on different in-school predictors and demographic characteristics. Burnes et al (2018) found that high-school SWD being involved in their IEP, interacting with others, and receiving support from their community predict PSO. Sprunger et al (2018) recommended that in order to improve PSO, special-education teachers should incorporate both academic and work components into high-school transition plans and receive professional development focused on transition programming.…”
Section: Introductionmentioning
confidence: 94%